A Mixed-Methods Systematic Review of the Effectiveness and Experiences of Quality Improvement Interventions in Radiology. Issue 1 (January 2022) - Jabin, MD Shafiqur Rahman; Schultz, Tim; Mandel, Catherine; Bessen, Taryn; Hibbert, Peter; Wiles, Louise; Runciman, William
Abstract : Objective: This study aimed to compile and synthesize evidence regarding the effectiveness of quality improvement interventions in radiology and the experiences and perspectives of staff and patients. Methods: Databases searched for both published and unpublished studies were as follows: EMBASE, MEDLINE, CINAHL, Joanna Briggs Institute, Cochrane Central Register of Controlled Trials, PsycINFO, Scopus, Web of Science, Mednar, Trove, Google Gray, OCLC WorldCat, and Dissertations and Theses. This review included both qualitative and quantitative studies of patients undergoing radiological examinations and/or medical imaging health care professionals; a broad range of quality improvement interventions including introduction of health information technology, effects of training and education, improved reporting, safety programs, and medical devices; the experiences and perspectives of staff and patients; context of radiological setting; a broad range of outcomes including patient safety; and a result-based convergent synthesis design. Results: Eighteen studies were selected from 4846 identified by a systematic literature search. Five groups of interventions were identified: health information technology (n = 6), training and education (n = 6), immediate and critical reporting (n = 3), safety programs (n = 2), and the introduction of mobile radiography (n = 1), with demonstrated improvements in outcomes, such as improved operational and workflow efficiency, report turnaround time, and teamwork and communication. Conclusions: The findings were constrained by the limited range of interventions and outcome measures. Further research should be conducted with study designs that might produce findings that are more generalizable, examine the other dimensions of quality, and address the issues of cost and risk versus benefit.